2013
DOI: 10.1097/htr.0b013e318255ceae
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Mild TBI and Postconcussive Symptoms in a Peacetime Active Duty Military Population

Abstract: Past experience of MTBI may be a risk factor for increased symptom difficulty for several months postinjury. Clinicians should ascertain lifetime history of brain injury when evaluating patients for MTBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 35 publications
3
30
2
Order By: Relevance
“…Postconcussive syndrome may be present in cases in which these symptoms associated with breaching and other repeated low-level blast exposure are prolonged. 12,16,19,27,[31][32][33] Clinical diagnoses were outside the scope of this survey, but given the observation of symptoms interfering with daily activity, blast surveillance may be warranted in those professional communities exposed to occupational blast. 34 There are a number of limitations to this survey that should be noted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postconcussive syndrome may be present in cases in which these symptoms associated with breaching and other repeated low-level blast exposure are prolonged. 12,16,19,27,[31][32][33] Clinical diagnoses were outside the scope of this survey, but given the observation of symptoms interfering with daily activity, blast surveillance may be warranted in those professional communities exposed to occupational blast. 34 There are a number of limitations to this survey that should be noted.…”
Section: Discussionmentioning
confidence: 99%
“…Such singleitem descriptors, however, have been reported in similar research. 12 Finally, the survey did not elicit deployment histories or address specifically whether a subject has experienced any traumatic events. These limitations could be mitigated by the inclusion of the comparison group, subject to the same considerations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk for persistent post-concussive symptoms and neurocognitive impairment following multiple concussions may depend on when they occurred-how close together and how recent. 20,42 Second, information about prior concussions was collected by retrospective self-report. Confirmation of concussion diagnosis and objective measures of injury severity were not available.…”
Section: Limitationsmentioning
confidence: 99%
“…8 A study of deployed U.S. service members found that 87% of second concussions occurred within 30 days of the initial injury, and that severity of the second injury (but not the first) was associated with higher use of mental health and neurological services during the 2 years after injury. 9 This is of concern because early evidence suggests that close temporal proximity of multiple head injuries is associated with poorer recovery.…”
Section: Introductionmentioning
confidence: 99%